Strategi Penghimpunan Dana Pihak Ketiga pada Bank Syariah Menggunakan Metode Kualitatif Deskripsi - Aisyah Amelia Purba; Noer Natasya; Mawwadah Irham (Universitas 45 Surabaya, 2025)
This study aims to analyze the strategy of collecting third party funds applied by Islamic banks. The research method used is qualitative descriptive, which allows researchers to describe the phenomenon in depth and detail. Data were collected through in-depth interviews with Islamic bank managers and analysis of related documents. The results of the study indicate that Islamic banks use various strategies to attract third party funds, including socialization of Islamic products, improving customer service, and cooperation with other financial institutions. The challenges faced include the lack of public understanding of Islamic banking and competition with conventional banks. This study provides insight into the importance of education and product innovation in increasing third party fund collection in Islamic banks.